2005
DOI: 10.1159/000089556
|View full text |Cite
|
Sign up to set email alerts
|

Insights into GABA Receptor Signalling in TM3 Leydig Cells

Abstract: γ-Aminobutyric acid (GABA) is an emerging signalling molecule in endocrine organs, since it is produced by endocrine cells and acts via GABAA receptors in a paracrine/autocrine fashion. Testicular Leydig cells are producers and targets for GABA. These cells express GABAA receptor subunits and in the murine Leydig cell line TM3 pharmacological activation leads to increased proliferation. The signalling pathway of GABA in these cells is not known in this study. We therefore attempted to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 120 publications
0
10
0
1
Order By: Relevance
“…We have also observed that GABA up-regulates expression of mRNA for the AC9 isoform [M. González et al, unpublished data]. Although GABA A receptors are typically associated with ionic events (gating of Cl – currents and changes in resting membrane potential), recent evidence supports additional roles including the regulation of the levels of several mRNA transcripts [44, 45]. …”
Section: Discussionmentioning
confidence: 86%
“…We have also observed that GABA up-regulates expression of mRNA for the AC9 isoform [M. González et al, unpublished data]. Although GABA A receptors are typically associated with ionic events (gating of Cl – currents and changes in resting membrane potential), recent evidence supports additional roles including the regulation of the levels of several mRNA transcripts [44, 45]. …”
Section: Discussionmentioning
confidence: 86%
“…GABA acts through a paracrine or autocrine mechanism via GABAA receptor activation [37]. This agent may play a similar role as a signalling molecule in endocrine organs and can for example inhibit the serotonin secretion [38].…”
Section: Discussionmentioning
confidence: 99%
“…GABA is a major inhibitory neurotransmitter in the mammalian nervous system (14) and functions through a paracrine or autocrine effect via GABA A receptor activation (13). More recently, it has become apparent that this agent may play a similar role as a signaling molecule in endocrine organs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus GABA and GABA receptors have been identified in peripheral endocrine organs, including growth hormone cells of the anterior pituitary lobe (17), in pancreatic islets (43), and in the testis of human and rodents (18). It is thought that GABA may regulate the synthesis and release of hormones in an autocrine/ paracrine manner (13). In Mastomys ileal EC cells, GABA A dose dependently inhibited basal and adrenergic-stimulated serotonin secretion with IC 50 s of 3 ϫ 10 Ϫ10 and 4 ϫ 10 Ϫ10 M, respectively.…”
Section: Discussionmentioning
confidence: 99%